1976
DOI: 10.1083/jcb.71.1.303
|View full text |Cite
|
Sign up to set email alerts
|

Cytochalasin B inhibits actin-related gelation of HeLa cell extracts.

Abstract: When the 100,000 g supernatant fraction (extract) of HeLa cells lysed in a buffer containing sucrose, ATP, DTE, EGTA, imidazole, and Triton X-100 is incubated at 25 degrees C, it gels, and actin and a HMWP are progressively enriched in the extract and in gel isolated from extract. CB (greater than or equal to 0.25 muM) inhibits gelation and specifically lowers the concentrations of actin and the HMWP in the fraction which sediments at 100,000 g after incubation. These results indicate that actin and HMWP are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…Since that time, studies on fractionation and ultrastructure of the cytoplasm and on the Ca ++ and ATP requirements for movement and consistency changes (24,30,31,32) have shown that rapid changes in the organization and interactions of actin and myosin most likely provide the molecular machinery for these changes. Recently, the studies on control of movement and consistency change by Ca ++ and ATP have been extended to cultured mammalian cells (14).The ability of cytoplasmic extracts to jell was recognized more recently, and it has been related to actin (22), actin and a high molecular weight actin-binding protein (4,29,34,35), actin and two other proteins (15, 16), or actin and several low molecular weight proteins (20). The gels formed by three of these cytoplasmic extracts can shrink spontaneously (4,22,29), and the incorporation of myosin into the shrunken gels has suggested that interactions of actin and myosin induce gel shrinkage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, studies on fractionation and ultrastructure of the cytoplasm and on the Ca ++ and ATP requirements for movement and consistency changes (24,30,31,32) have shown that rapid changes in the organization and interactions of actin and myosin most likely provide the molecular machinery for these changes. Recently, the studies on control of movement and consistency change by Ca ++ and ATP have been extended to cultured mammalian cells (14).The ability of cytoplasmic extracts to jell was recognized more recently, and it has been related to actin (22), actin and a high molecular weight actin-binding protein (4,29,34,35), actin and two other proteins (15, 16), or actin and several low molecular weight proteins (20). The gels formed by three of these cytoplasmic extracts can shrink spontaneously (4,22,29), and the incorporation of myosin into the shrunken gels has suggested that interactions of actin and myosin induce gel shrinkage.…”
mentioning
confidence: 99%
“…The ability of cytoplasmic extracts to jell was recognized more recently, and it has been related to actin (22), actin and a high molecular weight actin-binding protein (4,29,34,35), actin and two other proteins (15,16), or actin and several low molecular weight proteins (20). The gels formed by three of these cytoplasmic extracts can shrink spontaneously (4,22,29), and the incorporation of myosin into the shrunken gels has suggested that interactions of actin and myosin induce gel shrinkage.…”
mentioning
confidence: 99%
“…HMWPs that interact with actin have been implicated in cytoplasmic consistency changes (3,10,11,(13)(14)(15)19). Macrophage ABP and smooth muscle filamin have been isolated and appear to be similar (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation has made possible the comparison of HMWP isolated from cultured fibroblasts with ABP and filamin. We have adopted the general term "HMWP" (19) to avoid additional terminology; precise comparison of the three proteins awaits amino acid sequence determination to unequivocally demonstrate their proposed identity (9,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation